Implementation of New Student Admissions at Elementary School 07 Sungai Beremas, West Pasaman Regency: A SWOT Analysis Approach - Ahyarti, Ayra; Ningsih, Setya; Rusdinal, Rusdinal; Anisah, Anisah; Setiawati, Merika (Postgraduate School, Universitas Negeri Padang, 2024)
The study aims to offer actionable insights to improve student enrollment rates and enhance recruitment strategies. Using a qualitative descriptive approach and a SWOT analysis framework, the study explores both internal and external factors influencing the New Student Admissions (NSA). Key findings reveal that the school implements NSA through structured planning, which includes evaluating capacity and class size, setting transparent admission criteria, and adhering to Standard Operating Procedures (SOPs). The admission process comprises three main stages: registration, announcement of accepted students, and re-registration. The school leverages its strengths, such as a strong reputation, strategic location, and competent educators, while addressing weaknesses like limited promotion and outdated enrollment systems. Opportunities, including population growth and government support, are strategically utilized, while threats like competition from neighboring schools and zoning policies are mitigated. The study concludes that a well-structured NSA process, combined with insights from SWOT analysis, enhances the school’s ability to attract and retain students. Recommendations focus on improving promotional outreach, investing in technological upgrades, and fostering community engagement to ensure equitable and quality education.